Increasing the prestige of local self-government bodies and the effectiveness of activities should begin in the process of studying at the university - E. S. Shugrina (Правоприменение)
The subject of the research are the materials of judicial practice (texts of court decisions and information sources, the content of information about the results of court hearings), data from sociological surveys.The purpose of the article is to identify the relationship between the knowledge of municipal law, local self-government or urbanism obtained during training at a university and subsequent professional activities related to local self-government carried out at different levels of public authority.The methodology. A comprehensive methodology was used, including legal and sociological research methods. Formal legal, legal technical and comparative legal were used among the legal methods. The sociological methods include the method of expert survey and the method of content analysis, which makes it possible to reveal the real position of the respondent, if he wants to disguise it not only the positions expressed, but also the words actually used were analyzed. The most repeatable ones were identified with the help of special software products.The main results, scope of application. Quite significant amendments were made to the Russian Constitution in 2020. One of the novels concerns a unified system of public power, the inclusion of a new term in the text of the constitution. The implementation of these novels in the legislation on local self-government is expected after the completion of the formation of the updated composition of the Federal Assembly. For this, it is necessary not only to reveal the term itself and list the levels of public authority, but also to establish new principles of their relationship, incl. in a sense, uniform standards, rules and requirements for state and local authorities. One of the possible consequences of this may be an increase in the prestige of work in local self-government bodies, a change in attitudes towards work in local self-government bodies.Conclusions. The analysis of the materials of law enforcement practice, the data of opinion polls on trust in local self-government bodies, attitude to the results of the work of local self-government bodies and their officials show that of all levels of government the municipal level is least trusted. Unfortunately, such an attitude begins to form in the process of training future employees of public authorities at different levels.